The Impact of Stress Levels on Sleep Quality and Menstrual Patterns in Midwifery Students at the Ministry of Health Polytechnic of Padang - Naomi Isabella Hutabarat; Rahmaini Fitri Harahap; Aminah; Elvina Sari Sinaga; Widya Nengsih (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
This study aims to analyze the relationship between stress levels, sleep quality, and menstrual patterns in female Midwifery students at the Padang Ministry of Health Polytechnic. High academic stress in students often impacts their physical and mental health, including sleep quality and menstrual patterns. The study design used a correlational cross-sectional approach, involving 90 female students from the 2017-2019 intake who were selected using a purposive sampling technique. Data were collected through questionnaires to measure stress levels (Perceived Stress Scale), sleep quality (Pittsburgh Sleep Quality Index), and menstrual patterns. The results showed a significant relationship between stress levels and sleep quality (p = 0.007), with female students experiencing high stress tending to have poor sleep quality. However, no significant relationship was found between stress levels and menstrual patterns (p = 0.849), indicating that factors other than stress, such as diet and physical activity, may play a greater role in influencing menstrual patterns. This study recommends that educational institutions implement stress management programs to improve the quality of life and health of female students, especially in managing high academic stress.